Contribution to the knowledge of Chinese Meconematinae (Orthoptera: Tettigoniidae) I: One new species of Neocyrtopsis Liu & Zhang, 2007 with key to species - Bian, Xun; Lu, Xiangyi; Zhang, Qianwen (Zootaxa, 2022)
This paper describes one new species of Neocyrtopsis Liu & Zhang, 2007 and provides the key to all the species. All type specimens are deposited in Guangxi Normal University.